Independence Character Building Strategies of I'dadiyah Students at Campus 1 of DDI Mangkoso Islamic Boarding School - Hikma Nurawan; Muzdalifah Muhammadun; Abd. Halim; St. Nurhayati; Ambo Dalle (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to analyze: 1) The independence character of I'dadiyah students, 2) Factors influencing the independence character of I'dadiyah students, and 3) Strategies of DDI Mangkoso Islamic Boarding School in fostering the independence character of I'dadiyah students. This study is a qualitative research using a case study research design, with data types consisting of subjects and sources such as mentors, students, and parents of I'dadiyah students. The data collection stages involve observation, in-depth interviews, and documentation. Data processing is done using N Vivo 12 Plus software. Data analysis includes data reduction, data presentation, conclusion drawing, and verification. The validity testing techniques used are credibility and dependability tests. Research findings: 1) The independence character of I'dadiyah students at Campus 1 of DDI Mangkoso Islamic Boarding School includes: the ability to self-regulate, responsibility for duties and obligations, self-control with initiative, problem-solving skills, discipline compliance, self-confidence, independence from other student companions, and strong self-belief. 2) Factors influencing the increased independence character of I'dadiyah students are obtained from research results, including parental support, daily schedules, extracurricular activities, collaboration among mentors, mentor patience, good communication with parents, the boarding school environment, providing advice and motivation, giving rewards or praise, and maintaining positive peer relationships. 3) The strategies of DDI Mangkoso Islamic Boarding School in fostering the independence character of I'dadiyah students obtained from research results include habituation, role modeling, effective communication, giving reprimands or punishments, and regulating the students' clothing.